ANALISIS PENGARUH DISIPLIN KERJA, STRESS KERJA, DAN MOTIVASI KERJA TERHADAP KINERJA PEGAWAI (Studi pada Pegawai Dinas Perkebunan Provinsi Jawa Tengah) - Luki Haryuni, 10.05.51.0146 (Students Journal of Economic and Management, 2014)
Empirical phenomena found in the research shows that the realization of annual performance Plantation Office of Central Java Province has not been able to meet the targets set by the institution which is an indication that the performance of employees in the Department of Horticulture of Central Java Province is low. From the above it can be concluded that the issues raised in this study is: